Biogeometry energy and implications in design interior spaces" (Al-Academy, 2025)
The human being is a kinetic energy system that is constantly exchanging with the energies in his surrounding environment، He is affected by it negatively and positively according to its beneficial or harmful effect، so he is exposed within the interior space to a group of energies that affect his behavior and comfort، such as electrical energy، magnetism، light energy، color، sound، and matter، which is reflected in the quality of the interior space and the vital balance in the design، The sources of energy that supply a person and help him perform his vital functions vary in his internal environment، and there is a type of subtle energy that flows through seven centers and is linked to the various physical organs، organized energy is introduced into all types of energies and then the function is restored to balance، Both the laws of resonance and carrier vibration waves are used to do this task، The current research presents Biogeometry relationships and their implications in the design of interior spaces، which achieves direct or indirect solutions in interior design، The research includes two sections، the first of which is the concept of biogeometrics in interior design، and the second section of interior space and the expressiveness of place، The research presented a number of conclusions، the most important of which are: Distributing lighting and carefully determining its intensity creates positive، beneficial energy in the interior spaces of hospitals that helps the patient rest and relax، The connection of interior design with its exterior achieves psychological and physiological positives for humans، which adds special comfort and attractiveness to interior spaces، in addition to providing positive energy in interior spaces، The research also provides a set of recommendations and finally a list of sources.